Penerapan Partial Credit Model (PCM) Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Perbaikan Peralatan Listrik Pada Kelas XI Titl Di SMK Negeri 1 Kediri - Wisnu Deni Arif; Tri Rijanto; Rina Harimurti; Yulia Fransisca (Politeknik Kampar, 2024)
The learning process carried out by teachers in schools is a very important activity in improving the quality of education. The learning process carried out by the teacher cannot be separated from the use of instruments in the form of questions that will be presented to determine the level of students' critical thinking. The use of the right questions is very important to support the learning process in the future. One of them is a question based on the partial credit model to determine the level of critical thinking of students which is considered suitable to be implemented in the learning process. This study aims to determine the validity and reliability of the partial credit model instrument in the subject of electrical equipment repair and to determine the position of respondents and items on the wright map. The research method used is an experimental method in the form of a One-Shot Case Study. The experimental subjects were students of class XI TITL 2 at SMK Negeri 1 Kediri. Then to analyze and process data using ministep software. The results showed that the partial credit model based question instrument was declared valid for use with the unidimensionality test results obtained by the raw variance explained by measures measurement result of 40.4%, the partial credit model based item instrument was stated to be reliable with the item reliability rating result of 0.93 and 0.94, obtained person reliability values of 0.68 and 0.70, and obtained values from crombach alpha of 0.69, analysis of the wright map obtained item measures and person measures on the wright map showing the distribution of item difficulty and person abilities with limitations logit values 2 to -2 with equivalent person and item positions, so it can be concluded that the instrument can be used to measure the person's ability level.